A Computational Analysis of the Influence of a Pressure Wire in Evaluating Coronary Stenosis - Jie Yi; Fang-Bao Tian; Anne Simmons; Tracie Barber (Fluids, 2021)
Cardiovascular disease is one of the world’s leading causes of morbidity and mortality. Fractional flow reserve (FFR) was proposed in the 1990s to more accurately evaluate the functional severity of intermediate coronary stenosis, and it is currently the gold standard in cardiac catheterization laboratories where coronary pressure and flow are routinely obtained. The clinical measurement of FFR relies on a pressure wire for the recording of pressures; however, in computational fluid dynamics studies, an FFR is frequently predicted using a wire-absent model. We aim to investigate the influence of the physical presence of a 0.014-inch (≈0.36 mm) pressure wire in the calculation of virtual FFR. Ideal and patient-specific models were simulated with the absence and presence of a pressure wire. The computed FFR reduced from 0.96 to 0.93 after inserting a wire in a 3-mm non-stenosed (pipe) ideal model. In mild stenotic cases, the difference in FFR between the wire-absent and wire-included models was slight. The overestimation in severe case was large but is of less clinical significance because, in practice, this tight lesion does not require sophisticated measurement to be considered critical. However, an absence of the pressure wire in simulations could contribute to an over-evaluation for an intermediate coronary stenosis.